أساليب التعويض وارضاء الذات لدى الشعراء الصعاليك مقاربة نفسية - زيتوني, فائزة (جامعة الوادي - university of Eloued, 2022)
ملخص انبثقت حركة اللصوصية في العصر الجاهلي من نفوس عافت الذل والخنوع للقيود التي فرضتها عليهم القبيلة أو البيئة والظروف السياسية والاجتماعية، فهاموا في الأرض رافعين لواء الثورة والتمرد ضد كل تلك القيود، وهو ما تمليه النفس البشرية متى ما استشعرت الظلم والاضطهاد؛ فكان أن برزت فئة من اللصوص المبدعين اتخذوا من الشعر وموضوعاته متنفسا لهم يعبرون من خلاله عن معاناتهم أثناء سعيهم لإثبات ذواتهم. ولأنّ من أهم مقومات الابداع الشعري لدى الشعراء الصعاليك هي الدوافع النفسية والنوازع الداخلية للذات المقهورة؛ التي وجدت في النظم متنفسا وسبيلا للتفريغ والبوح بل والتعويض عما تعيشه الذات من مكبوتات وآلام وتهميش واقصاء؛ لذا يعتبر الغوص في الأساليب والحيل التي مارسها الصعاليك للترويح عما في نفوسهم من وجع مجالا خصبا ومادة دسمة تستحقّ البحث. Abstract The Sa’alik movement in the pre-Islamic era emerged as a reaction to the oppression and restrictions imposed by the tribe and the social and political environment. The adherents of the Sa’alik movement rebelled against these restrictions by choosing a life of banditry. It was that a group of creative thieves emerged who took poetry And because one of the most important components of poetic creativity among the Sa’alik poets are the psychological motives and internal impulses of the oppressed self, they have found in poetry a way to express their frustrations and repressed agonies as well as a way to reveal the extent to which they were marginalized. Therefore, an examination of the ways in which these poets to express themselves and their predicaments is a worthy pursuit and deserves the attention of critics because it is a promising area of research.
Methods Of Compensation And Self-satisfaction Among In The Sa'alik Poets A Psychological Approach
مقال
Keywords: لصعاليك؛ المجتمع؛ الاقصاء؛ التعويض؛ الذاتا; Sa’alik; exclusion; the society; compensation; Self